Ms. LaGrange is strange! - Gutman, Dan.; Paillot, Jim (New York : HarperTrophy, 2005)
The new lunch lady at Ella Mentry School, Ms. LaGrange, writes secret messages in the mashed potatoes and is trying to get the students to eat healthier foods.
3.8
3-6
3-6
650
Keywords: Schools -- Fiction; School lunchrooms, cafeterias, etc. -- Fiction; Food -- Fiction; Humorous stories; School stories; Food -- Fiction; Humorous fiction